STERILIZATION AND DISINFECTANTS USED IN A DENTAL OFFICE- A REVIEW - S, Prashanth; G, Preethi; Raman, Rajesh; Krishnan, Balaji; Anison, Job; varghese, Sunil; K, Mahalakshmi (Journal of Biomedical and Pharmaceutical Research, 2020)
As dentists, we must disinfect and clean all equipment’s and countertops between patients with a recommended hospital-grade bactericidal product. Non visible blood and saliva does not mean it is absent on environmental surfaces. Blood and saliva are present throughout dental treatment. If a patient becomes ill as a result of an exposure to a pathogen or a bacterium that is later found in our dental office surfaces, the employer and/or dentist is at risk of being responsible for the patient’s illness and associated compensatory damages. Understanding and recognizing the risk of disease will drastically reduce patient illness, practice liability and employee illnesses. Dentists cannot pretend that this is only a theoretical problem. Therefore the dental community needs to stay updated of the rapidly evolving standard of care and do its best to comply with the standard of care in daily practice. Key Words: Sterilization, Chemical Disinfection, Fumigation, Pathogens.